Molecular Confirmation of the Causative Agents of Diarrhea and Its Antimicrobial Susceptibility Tests (Central Asian Journal of Medical Sciences, 2023)
Objectives: This study aimed to investigate molecular confirmation of the causative agents of diarrhea and its antimicrobial susceptibility tests in the samples collected from patients who have symptoms of diarrhea. There is a relative lack of diagnostic studies on the causative agents of diarrhea in Mongolia, especially on the causative agents of bacterial diarrhea and their antibiotic susceptibility. Methods: A rectal swab and stool sample were taken from 187 patients admitted to the NCCD Mongolia with a diagnosis of diarrhea and infection between June 2018 and April 2020 using a hospital-based instantaneous survey model, and bacteriology, molecular biology, and antibiotic susceptibility testing were performed at the laboratory of Bacteriology and Immunology, Institute of Veterinary Medicine. Results: Of the 187 samples, N=127 (67.9%), p